2D time‐domain numerical Maxwell/transport modeling for THz distributed gallium nitride transferred electron device. (24th January 2017) - Dalle, Christophe
Abstract: The potential of gallium nitride–distributed transferred electron device is theoretically investigated for the realization of terahertz radio frequency (RF) power sources. The device numerical physical modeling relies on a 2D time‐domain electromagnetism/transport simulator. It is based on the coupled solution of the Maxwell and energy‐momentum macroscopic transport equations. The study is focused on the analysis of the device complex internal RF operation. The device technological and geometrical structure is optimized for an RF operation at 1 THz. The time and space, local and functional quantities are analyzed following both electromagnetic and quasi‐electrostatic approaches. We finally conclude on the feasibility of such a device.